Kesiapan Guru Taman Kanak-Kanak Dalam Melaksanakan Pembelajaran Daring Selama Pandemi Coronavirus Disease 2019 - Yane Zelvionita; Asdi Wirman (Jurnal Family Education, 2021)
This study aims to determine the readiness of Kindergarten teachers in X Koto sub-district in utilizing information and communication technology in online learning during the Covid-19 pandemic. Online learning in kindergarten in District X Koto is the first time so that the teacher looks stuttering in its implementation. This type of research is descriptive quantitative. This research was conducted in District X Koto. Sampling of the population of teachers in this study was carried out with purposive random sampling technique. The main characteristic of this sampling is that the sample members are selected specifically based on the research objectives. Data collection is done directly by distributing questionnaires. This study found that the readiness of kindergarten teachers in carrying out online learning during the Covid-19 pandemic was in the ready category. This readiness is seen from the indicators of the use of ICT in preparing learning materials, the use of ICT as a learning resource and the use of ICT in parenting. Meanwhile, teachers are still quite ready in the use of ICT as a medium of learning and evaluation of learning.